The Effectiveness of a Proposed Program Based on the Costa Model of Habits of Mind (H.o.M) on the Development of Creative Thinking Abilities (C.T.A) amongst Gifted Students in Jordan. - Mahmoud Ghazi Ewies, Aznan Che Ahmad,Aswati Hamzah (International Journal of Advanced Science and Technology, 2020)
This research paper targeted at determining the role of the effectiveness of a Proposed Program based on the Costa Model of Habits of Mind (H.o.M) on the Development of Creative Thinking Abilities (C.T.A) amongst Gifted Students in Jordan. Quasi-Experimental techniques were applied to explore the effectiveness of the training program on creative thinking abilities. 60 gifted students comprising were chosen randomly from the King Abdullah II schools for excellence (Madaba branch). Two control and experimental groups were formed, each has 30 gifted students. Torrance’s verbal (Form A) test was used to measure the students’ Creative Thinking Abilities (C.T.A). Data were collected using a quantitative technique. The results presented the presence of a significant difference between the groups (after implementing the Habits of Mind (H.o.M) training program) in regard to the increase of the Creative Thinking abilities of the gifted student. In the same context, the results of this research paper support the effectiveness of the specialized training programs on enhancing students’ Creative Thinking abilities.